Associations between the gut microbiota at one-year and neurodevelopment in children from the SEPAGES cohort - Aline Davias; Sarah Lyon-Caen; Nina Iszatt; Celine Monot; Yamina Rayah; Zehra Esra Ilhan; Karine Guichardet; Sam Bayat; Séverine Valmary-Degano; Gina Muckle; Merete Eggesbø; Patricia Lepage; et al. (Brain, Behavior, & Immunity - Health, 2025)
Fundamental research indicates a communication between the gut microbiota and the central nervous system, referred to as the microbiota-gut-brain axis. This link is little characterized in humans in the general population. We prospectively investigated the relationships between the gut microbiota composition of one-year-old children and neurodevelopment parameters at 2 and 3 years of age. Within the SEPAGES French couple-child cohort, we profiled gut microbiota by sequencing the V3-V4 region of the 16S rRNA gene from stool samples in 356 children at 12 months of age. We later assessed children's neurodevelopment through validated tests (CBCL at 2 years, and SRS-2, BRIEF-P and WPPSI-IV at 3 years). Microbial α-diversity indices, the 4 most abundant phyla, and the 46 most abundant genera were analyzed for their relations with neurodevelopmental parameters using multiple linear regression, while associations of β-diversity with neurodevelopment were examined through PERMANOVA tests. α- and β-diversity indices were not associated with neurodevelopmental parameters in children. Suggestive associations were observed with taxonomy, but not maintained after correction for multiple comparisons: phyla Proteobacteria and Bacteroidetes tended to be associated with higher socio-emotional neurodevelopment assessed with different sub-scores; phylum Firmicutes with increased plan and organization problems; genera Lactococcus, Coprococcus, Oscillibacter, Clostridium XVIII, Veillonella, Parabacteroides, Subdoligranulum and Saccharibacteria genera incertae sedis with lower socio-emotional neurodevelopment, while genera Enterococcus and Butyricicoccus tended to be associated with higher socio-emotional neurodevelopment, assessed with different sub-scores. Within this generally healthy population, only suggestive associations were observed between gut microbiota composition and neurodevelopmental scores at 2 and 3 years. Larger studies are needed to examine a possibly weak link between the gut microbiota of one-year-old children and their neurodevelopment.